2016
DOI: 10.1371/journal.pone.0163117
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pain Communication following Multiple Group Memberships Salience Leads to a Relative Reduction in Pain-Related Brain Activity

Abstract: Pain is a fundamental human experience that triggers a range of social and psychological responses. In this study, we present behavioral and fMRI data to examine the effect of multiple group memberships salience on reported and neural indices of pain. We found that participants expressed higher levels of pain when more social group memberships were salient. This is consistent with the notion that pain itself motivates people to communicate their pain, and more so when multiple psychological resources are salie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…This implies the capacity to enlist social resources is a coping capacity unto itself. In line with this possibility, one recent study found that as we become aware of supportive resources, such as group membership, our willingness to report distressing experiences (i.e., pain) increases at the same time that our subjective experience of it decreases (Ferris, Jetten, Molenberghs, Bastian, & Karnadewi, 2016), suggesting that we can benefit inherently from eliciting support. However, it could also be theorized that this capacity is best applied flexibly, so that we expand and contract our social overtures according to the specific contexts we find ourselves in (Bonanno & Burton, 2013).…”
Section: Implications For Theorymentioning
confidence: 86%
“…This implies the capacity to enlist social resources is a coping capacity unto itself. In line with this possibility, one recent study found that as we become aware of supportive resources, such as group membership, our willingness to report distressing experiences (i.e., pain) increases at the same time that our subjective experience of it decreases (Ferris, Jetten, Molenberghs, Bastian, & Karnadewi, 2016), suggesting that we can benefit inherently from eliciting support. However, it could also be theorized that this capacity is best applied flexibly, so that we expand and contract our social overtures according to the specific contexts we find ourselves in (Bonanno & Burton, 2013).…”
Section: Implications For Theorymentioning
confidence: 86%
“…In the context of acquired brain injury belonging to multiple groups lowered depression symptoms because exposure to multiple groups gave participants the chance to practice and develop self-regulatory skills (Kinsella et al, 2020). The study of Ferris et al (2016) also showed that being part of multiple groups leads to an increase in communication about pain and this communication reduced brain activation in regions associated with pain. Being part of multiple groups is in this context, a resource that diminishes pain.…”
Section: Figurementioning
confidence: 99%
“…For example, physical pain has been found to promote prosocial behaviors, such as cooperation and trust, implicating the evolutionarily adaptive significance of pain ( Bastian et al. , 2014 ; Ferris et al. , 2016 ; Wang et al.…”
Section: Discussionmentioning
confidence: 99%